Cultural Gender Norms and Neighbourhood Exposure: Impacts on the Gender Gap in Math - Sanna Ericsson (Lund University, School of Economics and Management, Department of Economics, 2020)
This paper investigates the interaction between cultural norms and neighbourhood characteristics. I estimate the effect of cultural gender norms on the gender gap in math, and explore whether this effect is mitigated by municipality gender equality. I use high-quality Swedish administrative data on the results of national standardised math tests. To separate the effect of cultural gender norms from formal institutions, I estimate the effect of mothers' source-country gender norms on the gender gap in math for second-generation immigrants. By contrasting the outcomes of opposite-sex siblings, I show that the sibling gender gap in math increases with mothers' adherence to traditional gender norms; such that girls with more gender-traditional mothers perform worse relative to their brothers. To investigate whether the cultural gender norm effect can be mitigated by municipality gender equality, I exploit a refugee placement policy to obtain random variation in municipality characteristics. I show that municipality gender equality can almost completely mitigate the negative cultural norm effect. Taken together, my results imply that while cultural gender norms play an important role for the gender gap in math, they are not immune to the effects of neighbourhood exposure.
Keywords: I21; I24; J15; J16; Z13; 330; cultural gender norms; math gender gap; epidemiological approach; refugee placement policy; sibling fixed effects